2017
DOI: 10.1590/1678-98652017000300009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between taste sensitivity, preference for sweet and salty flavours, and nutritional status of adolescents from public schools

Abstract: ObjectiveThis study aimed to investigate the associations between taste sensitivity, preference for sweet and salty flavours, and nutritional status of adolescents in public schools. MethodsWe used a cross-sectional study involving 1,036 adolescents of both sexes, aged 10-19 years. Preference for sweet or salty flavours and preference for foods high in sugar or sodium were evaluated. Measurements of body mass index and taste flavour intensity recognition were conducted. ResultsMost participants were unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Thus, the relation between DT/RT and intensity perception in suprathreshold concentrations and sweet dietary intake is still not clearly defined (Hardikar et al., 2017; Tan & Tucker, 2019). However, alimentary patterns and enhanced hedonic liking of sweetness at high concentrations may result in a higher consumption of sweet food (dos Santos, Marreiros, da Silva, de Oliveira, & Cruz, 2017; Duffy, Hayes, Sullivan, & Faghri, 2009). Additionally, a dose‐dependent relationship has been described between suprathreshold intensity perception and hedonic liking (Jayasinghe et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relation between DT/RT and intensity perception in suprathreshold concentrations and sweet dietary intake is still not clearly defined (Hardikar et al., 2017; Tan & Tucker, 2019). However, alimentary patterns and enhanced hedonic liking of sweetness at high concentrations may result in a higher consumption of sweet food (dos Santos, Marreiros, da Silva, de Oliveira, & Cruz, 2017; Duffy, Hayes, Sullivan, & Faghri, 2009). Additionally, a dose‐dependent relationship has been described between suprathreshold intensity perception and hedonic liking (Jayasinghe et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Normal-weight adults have reported preferring sweet foods more than adults with obesity ( 22 ). A study characterizing adolescent tastes by genotype observed a higher intake of chocolate among individuals with obesity than normal weight ( 52 ) while in another study, a higher preference for salty foods was reported by overweight and obese adolescents ( 53 ). In our study, normal-weight individuals had higher energy intake from sweet foods compared with those with obesity who had the highest energy intake from neutral-tasting foods and both of savory and salty tasting foods.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in taste perception among individuals can also shape flavor preferences, influencing dietary intake and long-term eating habits [ 42 ]. Studies have demonstrated that genetic variations related to bitter taste, for instance, may be related to acceptance of feeding introduction [ 43 ], to food selectivity [ 44 ], and higher daily energy density from snacks in children aged 3 to 5 years [ 45 ].…”
Section: Introductionmentioning
confidence: 99%